NILAI PENDIDIKAN KARAKTER DALAM TRADISI KEAGAMAAN MASYARAKAT MUSLIM PAPUA BARAT - Akramun Nisa (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2020)
This research is an attempt to examine the meaning of character education in the religious traditions of the Muslim community in West Papua. The techniques used in the data collection process are interviews, observation and documentation. The results obtained indicate that the inherited tradition is obtained from the value of character education. Rather than the value of education, so is the religious value and the value of appreciation in the tradition of safar bathing, the sahur drum, discussing the night of prayer, the implementation of aqiqah and qurban, the descendant's maulid and the factual maulid, tombormark and khatib pickup tradition. Learning local character education based on local wisdom becomes an alternative consideration that involves and implements the values ​​of wisdom in the minds, paradigms, and beliefs of students by supporting the heart and reason in forming character.